2019
DOI: 10.2174/1871527317666181105112009
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-214-5p Released from Glioblastoma Cells Modulates Inflammatory Response of Microglia after Lipopolysaccharide Stimulation through Targeting CXCR5

Abstract: Background and Objective: Exosomes communicate inter-cellularly and miRNAs play critical roles in this scenario. MiR-214-5p was implicated in multiple tumors with diverse functions uncovered. However, whether miR-214-5p is mechanistically involved in glioblastoma, especially via exosomal pathway, is still elusive. Here we sought to comprehensively address the critical role of exosomal miR-214-5p in glioblastoma (GBM) microenvironment. Methods: The relative expression of miR-214-5p was determined by real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…It is also likely that this will impact on the contents of vesicles and exosomes produced by GBM/GSC, such as miRNAs, with consequences for regulation of glia and immune cells in the tumour microenvironment. 90 As such, alterations in the NAS/melatonin ratio have links to longstanding ideas regarding the nature of the tumour microenvironment and its influence on tumour survival, indicating that GBM/GSC may have a number of means in shaping this tumour microenvironment, including variations in the NAS/melatonin ratio. This suggests a dynamic 2-way interaction of tumour and tumour microenvironment, which would be modulated by levels of melatonin synthesis and uptake.…”
Section: International Journal Of Tryptophan Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also likely that this will impact on the contents of vesicles and exosomes produced by GBM/GSC, such as miRNAs, with consequences for regulation of glia and immune cells in the tumour microenvironment. 90 As such, alterations in the NAS/melatonin ratio have links to longstanding ideas regarding the nature of the tumour microenvironment and its influence on tumour survival, indicating that GBM/GSC may have a number of means in shaping this tumour microenvironment, including variations in the NAS/melatonin ratio. This suggests a dynamic 2-way interaction of tumour and tumour microenvironment, which would be modulated by levels of melatonin synthesis and uptake.…”
Section: International Journal Of Tryptophan Researchmentioning
confidence: 97%
“…It is also likely that this will impact on the contents of vesicles and exosomes produced by GBM/GSC, such as miRNAs, with consequences for regulation of glia and immune cells in the tumour microenvironment. 90…”
Section: Integrative Modelmentioning
confidence: 99%
“…The GBM microenvironment, reshaped through these modifications, may contribute to tumor progression. Other evidence on the cross-talk between GBM and microglia comes from the finding reported by Yang et al; they demonstrated that miR-214-5p, aberrantly upregulated in GBM cells, can be transferred to microglia, through exosomes, contributing to the suppression of microglial C-X-C motif chemokine receptor 5 (CXCR5), and, consequently, increasing the microglial secretion of inflammatory cytokines IL-6, IL-8, and TNF-α, which, in turn, favor a tumorsupportive microenvironment [77]. The microglial function appears to be modulated also by miRNAs belonging to the let-7 family [78].…”
Section: Mirnas Mediate the Cross-talk Between Gbm And Microglia Cellsmentioning
confidence: 98%
“…Briefly, conditioned medium and precipitation solution were mixed (1:1) and incubated (4 • C, overnight), and then serially, centrifuges were performed (10,000 × g for 30 min; 140,000 × g for 5 min at 4 • C) to get the GSC supernatant and the resultant EV pellet, which was re-suspended with 250-500 µl cell medium. The equal volume of EVs derived from GSCs was added to the microglia cells for 48 h of consecutive culture (9).…”
Section: Ev Isolationmentioning
confidence: 99%
“…Tumor-derived EVs may act on different types of immune cells, such as effector T cells, nature regulatory T cells, natural killer cells, and macrophages, which contributes to the induction and maintenance of the immune-suppression environment (7,8). Our previous data indicate that the EVs released from glioblastoma cells can transfer miR-214-5p to brain microglia/macrophages to modulate the corresponding inflammatory response that favors the survival of glioblastoma cells (9).…”
Section: Introductionmentioning
confidence: 99%